Design And Modelling Of Single-Phase Grid-Connected Photovoltaic At Low Voltage Network Using PSCAD Software - Hairi, Mohd Hendra; Kamarudin, Muhammad Nizam; Mohd Isira, Ahmad Sadhiqin; Hanaffi, Farhan; Ab Rahman, Azhan (Penerbit Universiti, UTeM, 2019)
The objective of this paper is to design and model a single-phase grid-connected photovoltaic (PV) system at low-voltage network. The system consists of PV as the main source of energy, single-phase inverter, Proportional Integral (PI) controller, low-pass filter, load, and lowvoltage distribution network. The model was developed using PSCAD-EMTDC software. The design was tested in terms of active power (P) and reactive power (Q) produced the to support the load demand. The results showed that the PV model was able to meet the load demand by properly tuning the PI controller. Simulation studies demonstrate the effectiveness of the controller and confirmed that the system are robust with acceptable performance